Bidirectional Regulation of Keratinocyte Proliferation and Apoptosis by Metformin via NLRP3 Inflammasome Pathway - TIAN Ke, LENG Qiufeng, LYU Jing, MIAO Guoying, WANG Xinhui, XIE Hui, LIU Qu, YAO Chunxia (Zhongguo quanke yixue, 2025)
Background Lichen planus is a chronic inflammatory disease of the skin and mucosa. Due to its unknown etiology, many patients have poor treatment effect, which seriously affects the quality of life. It is necessary to further study the pathogenesis of lichen planus to provide a new target for drug screening. Objective To investigate the effects of metformin on keratinocyte proliferation and apoptosis through NLRP3 inflammasome pathway. Methods Experiment period: 2020 to 2023. In vitro experiment, human immortalized keratinocytes (HaCaT) were divided into 4 groups: control group, lipopolysaccharide group (LPS group: 5 μg/mL), metformin group (Met group: 10 mmol/L), LPS combined with metformin group (LPS+Met group: metformin was treated with 10 mmol/L after LPS 5 μg/mL stimulation for 2 hours). In vivo experiments, BALB/c mice were used as research objects to induce psoriatic dermatitis model by applying imiquimod on the back skin, and metformin cream was prepared for treatment. The mice were randomly divided into 3 groups: control group, imiquimod group (IMQ group), and imiquimod plus metformin group (IMQ+Met group). Each group has 10 mice. Mice in the control group were smeared with petroleum jelly on the back, mice in the IMQ group were smeared with imiquimod ointment on the back, mice in the IMQ+Met group were smeared with metformin cream after 12 h of IMQ ointment. Once a day for seven consecutive days. Cell counting kit-8 (CCK-8) and flow cytometry were used to detect the effects of metformin on the proliferation and apoptosis of HaCaT cells. Western Blotting, enzyme-linked immunosorbent assay (ELISA) and Caspase-1 activity assay were used to detect the expression and activity of NOD-like receptor protein 3 (NLRP3) inflammasome pathway protein in HaCaT cells treated with metformin. Finally, hematoxylin-eosin (HE) staining and immunohistochemistry were used to detect the anti-inflammatory effect of metformin on imiquimod-induced psoriatic dermatitis in mice. Results The results of CCK-8 experiment showed that the 48 h survival rate of HaCaT cells in LPS, Met and LPS+Met groups were lower than that in control group, while the 48 h survival rate of HaCaT cells in LPS+Met group was higher than that in LPS group (P<0.05). Flow cytometry results indicated that the proportions of G2/M phase and apoptosis of HaCaT cells at 48 h in LPS and Met groups were higher than those in control group, while the proportion of G2/M phase and apoptosis of HaCaT cells at 48 h in LPS+Met group were lower than those in LPS group (P<0.05). Western Blotting results demonstrated that the expression of Caspase-1 p40, Caspase-1 p20, interleukin (IL) -1β and IL-18 proteins in NLRP3 inflammasome pathway of HaCaT cells in LPS and Met groups were higher than those in control group. The expression of Caspase-1 p40, Caspase-1 p20, IL-1β and IL-18 of HaCaT cells in LPS+Met group were lower than those in LPS group (P<0.05). ELISA results showed that the levels of IL-1β, IL-18 and relative activity of Caspase-1 in NLRP3 inflammasome pathway of HaCaT cells in LPS and Met groups were higher than those in control group. The levels of IL-1β, IL-18 and relative activity of Caspase-1 of HaCaT cells in LPS+Met group were lower than those in LPS group (P<0.05). Metformin application in IMQ+Met group significantly improved the imiquimod skin damage observed by HE staining. Immunohistochemical results reported that the expressions of NLRP3, Caspase-1, IL-1β and IL-18 were significantly decreased in IMQ+Met group. Conclusion Metformin bidirectional regulates the proliferation and apoptosis of skin keratinocytes through the NLRP3 inflammasome pathway, and can improve the skin damage induced by imiquimod in psoriasis mice, which is expected to provide a theoretical basis for the clinical use of metformin in the treatment of lichen planus.